2020
DOI: 10.18070/erciyesiibd.663413
|View full text |Cite
|
Sign up to set email alerts
|

Değişim Yönetimi ile Ücret ve Ödüllendirme Sistemi Arasındaki İlişki: Sivil Havacılık Sektöründe Faaliyet Gösteren Yer Hizmetleri İşletmelerinde Bir Araştırma

Abstract: Bu çalışmanın amacı, sivil havacılık sektöründe faaliyet gösteren yer hizmetleri işletmelerinde değişim yönetimi ile ücret ve ödüllendirme sistemi arasındaki ilişkiyi tespit etmektir. Yer hizmetleri işletmelerinde çalışan üst ve orta düzey yöneticilere yapılan anket çalışmasına 171 yönetici katılmıştır. Araştırmanın sonucunda ise değişim yönetimi ile ücret ve ödüllendirme sistemi arasında güçlü bir ilişki olduğu tespit edilmiştir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…It is stated that organizations can respond to different demands from the environment thanks to these differentiations and thus can adapt to all different environmental conditions (Sherehiy, Karwowski & Layer, 2007). This view was supported by a global survey conducted by McKinsey & Company (2008), which revealed that businesses that can provide continuous change, can survive (Burnes & Jackson, 2011;Sucu, 2020).…”
Section: Organizational Changementioning
confidence: 98%
See 1 more Smart Citation
“…It is stated that organizations can respond to different demands from the environment thanks to these differentiations and thus can adapt to all different environmental conditions (Sherehiy, Karwowski & Layer, 2007). This view was supported by a global survey conducted by McKinsey & Company (2008), which revealed that businesses that can provide continuous change, can survive (Burnes & Jackson, 2011;Sucu, 2020).…”
Section: Organizational Changementioning
confidence: 98%
“…Güçlü & Şehitoğlu (2006) define change as the process of making decisions and implementing these decisions in order to be able to produce new ideas individually or organizationally at a level that can meet those needs by restructuring the organization in case the current situation is no longer adequate in the face of the needs of environmental conditions. Change, in the light of these definitions, can be defined as the transition of all elements and features from one state to another at the individual and organizational level as required by environmental conditions (Sucu, 2020).…”
Section: Organizational Changementioning
confidence: 99%